Effects of microclimate on soil moisture distribution in complex topography at the small watershed scale in the Anning River Region, Southwest China - Yafeng Lu; Wenguang Chen; Xiaoqing Chen; Zhengyang Li (Journal of Hydrology: Regional Studies)
Study region: Reshuihe watershed, located in the Anning River region of Southwest China. Study focus: This research meticulously monitors the spatiotemporal variations in soil moisture and climatic factors within the watershed. Its primary aim is to unravel the complex interplay and predominant influences of topo-climatic factors on soil moisture distribution across varying elevational gradients, aspects, and topographic positions. New hydrological insights for the study region: The results demonstrate that soil moisture levels increase with elevation during both dry and wet seasons, albeit with nonlinear rates of change. Detailed analysis reveals that soil moisture in the study area is primarily determined by topographic position, with aspect and elevation having secondary influences. Notably, the difference between dew point temperature and soil surface temperature, along with evapotranspiration, emerged as critical factors influencing soil moisture at mid- and low elevations during the wet season. Conversely, during the dry season, evapotranspiration and wind speed were identified as the principal factors affecting soil moisture across most elevations. This investigation advances the integration of topographical factors—position, aspect, and elevation—with essential physical processes such as condensation and evapotranspiration, delineating their pivotal roles in influencing soil moisture within mountainous landscapes. Additionally, it highlights the limitations of Soil Moisture Active Passive (SMAP) simulations in accurately capturing elevation-specific moisture variations in such terrains, pointing towards critical areas for improvement in soil moisture simulation.